2002
DOI: 10.1086/341682
|View full text |Cite
|
Sign up to set email alerts
|

Stellar Variability in a Survey of Field Stars

Abstract: ABSTRACT. We present results from a 5 night wide-field time-series photometric survey that detects variable field stars. We find that the fraction of stars whose light curves show variations depends on color and magnitude, reaching 17% for the brightest stars in this survey ( ) for which the photometric precision is best. The V ∼ 14 fraction of stars found to be variable is relatively high at colors bluer than the Sun and relatively low at colors similar to the Sun and increases again for stars redder than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
4

Year Published

2002
2002
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 28 publications
4
26
4
Order By: Relevance
“…In comparison to Everett et al (2002), who found an overall variability fraction of 1% in their weeklong sample, the fraction here is 3-4 times in field groups 01 and 19. However, the two fractions are roughly equivalent if the amplitude level for variability is limited to the photometric uncertainties in the Everett et al (2002) study. Figures 15 and 16 show the variability fraction of sources for the field groups as a function of B À V color for the most complete magnitude sample V ¼ 17:5À22:0.…”
Section: Variability Fractions By Magnitude and Colorcontrasting
confidence: 89%
See 1 more Smart Citation
“…In comparison to Everett et al (2002), who found an overall variability fraction of 1% in their weeklong sample, the fraction here is 3-4 times in field groups 01 and 19. However, the two fractions are roughly equivalent if the amplitude level for variability is limited to the photometric uncertainties in the Everett et al (2002) study. Figures 15 and 16 show the variability fraction of sources for the field groups as a function of B À V color for the most complete magnitude sample V ¼ 17:5À22:0.…”
Section: Variability Fractions By Magnitude and Colorcontrasting
confidence: 89%
“…Recently, wide-field temporal surveys have begun to catch up, going to deeper limits and becoming increasingly more common, such as the Bright Sky Variability Survey ( BSVS; Everett et al 2002), QUEST ( Vivas et al 2004), SuperMACHO ( Becker et al 2005), and the Faint Sky Variability Survey ( FSVS; Groot et al 2003), with a variety of different science goals and target populations, probing new areas in astrophysics. A survey like the FSVS with variability sampling over hours to years samples a large range of dynamical phenomena, including mass transfer events, pulsations, and stellar activity with amplitudes $0.01 and larger.…”
Section: Introductionmentioning
confidence: 99%
“…Wide field observations of field stars have also produced a number of new variable stars (e.g. Bakos et al 2002; Everett et al 2002; Hartman et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 6 displays the color-magnitude diagram, (B−R) versus R, to show difference of color distributions between pulsating and eclipsing stars. The left panel was made from the observation results of Everett et al (2002) with 222 variable stars. The right panel shows the diagram for 91 ROTSE-I δ Scuti stars whose B and R magnitudes were obtained from the USNO catalogue.…”
Section: Resultsmentioning
confidence: 99%